2012
DOI: 10.1143/jjap.51.07gd05
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical Effect Using Ultrasonic Atomizer at 2.4 MHz

Abstract: Sonochemical reactions were demonstrated using a commercial ultrasonic atomizer at 2.4 MHz. The influences of experimental conditions, bottom shape and glass thickness of reactors, irradiation method, and liquid height on the sonochemical yield were discussed. The sonochemical effect was evaluated by potassium iodide dosimetry and degradation of methylene blue. Direct and indirect irradiations were examined. The former had the highest yield. In the latter case, sonochemical yield decreased in the solution beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Recently, it has been indicated that the lag time for the nucleation of a PrP aggregate is dependent on the ultrasonic power, 9) which was determined using calorimetry and potassium iodide oxidation methods. 20) However, this method fails to identify the dominant nucleation mechanism because the ultrasonic power is related to almost all acoustic parameters. Considering that the cavitation bubble plays a central role in sonochemical reactions, [21][22][23] it is necessary to investigate the dependence of the aggregation phenomena on the acoustic pressures of fundamental and harmonics-wave modes individually.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been indicated that the lag time for the nucleation of a PrP aggregate is dependent on the ultrasonic power, 9) which was determined using calorimetry and potassium iodide oxidation methods. 20) However, this method fails to identify the dominant nucleation mechanism because the ultrasonic power is related to almost all acoustic parameters. Considering that the cavitation bubble plays a central role in sonochemical reactions, [21][22][23] it is necessary to investigate the dependence of the aggregation phenomena on the acoustic pressures of fundamental and harmonics-wave modes individually.…”
Section: Introductionmentioning
confidence: 99%
“…Methylene blue removal by 2.4 MHz ultrasonic atomisation was reportedly better under direct atomisation compared to indirect atomisation. 14 Methylene blue degradation was also noted during atomisation. 14 Kirpalani et al 15 sonicated KI solution under 1.7 and 2.4 MHz, they reported that cavitation yield reduced with frequency and also noted that the cavitation yield under 1.7 MHz was slightly lower than that of 640 kHz.…”
Section: Introductionmentioning
confidence: 98%
“…14 Methylene blue degradation was also noted during atomisation. 14 Kirpalani et al 15 sonicated KI solution under 1.7 and 2.4 MHz, they reported that cavitation yield reduced with frequency and also noted that the cavitation yield under 1.7 MHz was slightly lower than that of 640 kHz. Thangavadivel et al 16 reported DDT [1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane] degradation from aqueous solution under 1.6 MHz sonication.…”
Section: Introductionmentioning
confidence: 98%
“…5) Acoustic cavitation generated by highpower ultrasound has been used in sonochemistry. [6][7][8][9][10] The total ultrasonic power of equipment used in these fields is one of the key quantities for safety.…”
Section: Introductionmentioning
confidence: 99%